A living tribute to professor Marius Romme. Issue 4 (2nd October 2022) - Bullimore, Peter; Carson, Jerome
ABSTRACT: Professor Marius Romme has been one of the most influential psychiatrists of his generation. He revolutionized the approach to working with people who hear voices. This Living Tribute to Marius features short accounts by many of those he has worked with over the decades from both professional and lived experience perspectives. Thanks to his work and all those who have worked with him, hearing voices is no longer dismissed as a symptom of schizophrenia requiring medication, but as something to be understood in the context of each person's unique life history.